SISTEM INFORMASI TIM PENGGERAK PKK BERBASIS WEB PADA DESA KELAMBIR V KEBUN - Putra, Eka; Khairul, Khairul; Wijaya, Rian Farta; Harahap, Sutan Putra Nauli (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2024)
In Kelambir V Kebun Village, the Family Welfare Empowerment (PKK) Movers Team data storage process still uses manual methods. Data storage like this can cause unsafe data. Therefore, the researcher will create an information system for the Family Welfare Empowerment (PKK) Movers Team of the village of Kelambir V Kebun computerized which is sufficiently web-based which is php as the programming language and mysql xampp as the database. This study aims to create a Family Welfare Empowerment (PKK) Movers Team information system using php and mysql. This research was conducted in Kelambir V Kebun Village, North Sumatra Province. This research uses qualitative methods with data collection techniques by observation and literature study. From the problems that have been obtained so that the researcher can a solution from handling it by implementing a web-based application for the Kelambir V Kebun Village Family Welfare Empowerment (PKK) Team. It can be concluded that the application made by researchers can help the village of Kelambir V Kebun process data on the Family Welfare Empowerment Team quickly and safely. Based on black box and white box testing, it is found that the application made is feasible to use.